Economics : applications to agriculture and agribusiness - Roy, Ewell P. (Danville, Ill. Interstate Printers & Publishers, 1981)
Contents: Introduction; brief history of U. S. Agriculture; types of economic systems; types of business organizations in a capitalistic economy; the U. S. Monetary system and fiscal policy; macro-profile of the U. S. Economy.
Includes bibliographies and index.
Keywords: Quản trị kinh doanh